Policies and procedures for patient transfers from community clinics to emergency departments under the mental health act: Review and policy scan. (July 2020) - Neilson, Shane; Chittle, Andrea; Coleman, Terry; Kurdyak, Paul; Zaheer, Juveria
Abstract: Objective: The objective of this commentary is to summarize the few findings from the scientific literature pertaining to humane mental health transfer practices in the province of Ontario as well as the broader Canadian and international context. These findings are juxtaposed with a policing policy scan concerning the Ontario and Canadian contexts. The practice of default restraint use during transfers is surprisingly widespread practice, despite advocacy to the contrary, and is presented as the consequence of stigma and the lack of codified restriction of restraint use by police in their policy guidelines. Methods: (1) Literature search to discover relevant articles which were summarized using narrative review due to the lack of high-quality studies available in this area, and (2) Scan of publicly available policy documents in use by Ontario police agencies in March and April of 2018, as well as contacting several police agencies and community resources to review policies and procedures. Results: We review the available evidence on the use and impact of restraints in patient transfer to emergency departments from police settings, highlight police practices in four Ontario jurisdictions, and summarize recommendations from police and mental health advocates regarding mental health transfers. Discussion: Synthesizing the available evidence, policies, and procedures, we illustrate that the Ontario-wide variability in both who transfers PMI on a Form 1 to hospital and whether restraints are utilized reflect systemic failures to utilize least restrictive means of transfer. We offer a look at future areas of research and advocacy to improve practices in Canada.